2021
DOI: 10.1111/tops.12526
|View full text |Cite
|
Sign up to set email alerts
|

Integration by Parts: Collaboration and Topic Structure in the CogSci Community

Abstract: Is cognitive science interdisciplinary or multidisciplinary? We contribute to this debate by examining the authorship structure and topic similarity of contributions to the Cognitive Science Society from 2000 to 2019. Our analysis focuses on graph theoretic features of the co-authorship network-edge density, transitivity, and maximum subgraph size-as well as clustering within the space of scientific topics. We also combine structural and semantic information with an analysis of how authors choose their collabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…For instance, a bibliometric study based on the particular case of the journal Cognitive Science, which quantifies coauthorship networks, showed that this journal is among the best in this metric of interdisciplinarity compared to other journals in the social and natural sciences (Bergmann, Dale, Sattari, Heit, & Bhat, 2017). More recently, new studies show that, during the period between 2000 and 2019, the contributions to the Cognitive Science Society have become increasingly integrated, that is, more interdisciplinary and less multidisciplinary (DeStefano, Oey, Brockbank, & Vul, 2021). In addition, Alasehir and Acarturk (2022) also highlight that the scholarly domain of cognitive science has been exhibiting more manifest interdisciplinarity over the last decades.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a bibliometric study based on the particular case of the journal Cognitive Science, which quantifies coauthorship networks, showed that this journal is among the best in this metric of interdisciplinarity compared to other journals in the social and natural sciences (Bergmann, Dale, Sattari, Heit, & Bhat, 2017). More recently, new studies show that, during the period between 2000 and 2019, the contributions to the Cognitive Science Society have become increasingly integrated, that is, more interdisciplinary and less multidisciplinary (DeStefano, Oey, Brockbank, & Vul, 2021). In addition, Alasehir and Acarturk (2022) also highlight that the scholarly domain of cognitive science has been exhibiting more manifest interdisciplinarity over the last decades.…”
Section: Introductionmentioning
confidence: 99%